DAMPAK PERUBAHAN KAWASAN HUTAN MENJADI AREAL INDUSTRI BATUBARA TERHADAP KUALITAS AIR DI SEPANJANG DAS BERAU–KALIMANTAN TIMUR - Parwati, Ety; Soewardi, Kadarwan; Kusumastanto, Tridoyo; Kartasasmita, Mahdi; Nurjaya, I Wayan (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2011)
The study of landused change: forest area become coal industrial area and its impact in Total Suspended Solid is done by remote sensing data. The different combination channel of remote sensing data are taken to extract landuse and Total Suspended Solid (TSS) spatial information. The supervised classification is used for land used spatial extraction and otherwise for TSS, there is a specific algorithm; TSS = 3.8926 * exp (31.417*Red Band). The result showed that there was the relationship between landuse change from forest into coal industrial, shrub, paddy field, bareland and settlement area and the dynamic change of TSS along Berau watershed.